Die mite as ideologiese verskynsel : die versoeke na 'n nuwe mite in Postapartheid Suid-Afrika - Groenewald, Ilse Carla (Afrikaans and Netherlandic Studies, 2014)
The study aims at searching for a new myth in Post-Apartheid South Africa. This search was conducted by analysing myth as an ideological manifestation and thereby attempting to find a new myth in a country that has undergone a major ideological shift. The study roughly consists of three sections. Firstly, a detailed study was done to establish what exactly the concepts myth and ideology entail and how they are used within the framework of this dissertation. Secondly, the concept cultural memory is investigated, which includes an analysis of memory, history and history production. Thirdly, it includes a text analysis of the works of three South Africa authors. By looking at theoretical concepts on ideas, using Carl Jung's theories on the human psyche, Roland Barthes's theories on myth and Etienne Leroux's writing on the power of the myth and how it is used to mobilise ideas, idea transferral and how ideas eventually become ideolgies, is investigated.